Evaluasi Penerapan Whistleblowing System Pada PT X - Muhammad Bagaskara; Julian, Lufti (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
Companies that want to achieve their goals need good corporate governance. One of the supporting instruments is the whistleblowing system. However, there are still many fraud cases that occur in the private sector. This study aims to analyze the whistleblowing system or complaint handling system at PT X, which is one of the companies engaged in banking. This research uses qualitative methods and analytical descriptive methods. The instruments used are interviews and questionnaires. The results showed that although the implementation of the whistleblowing system at PT X has been carried out well, there are still some weaknesses. These weaknesses include employees who do not want to take reports to the whistleblowing system and there is no reward system for whistleblowers. This research also provides suggestions for improving the implementation of the whistleblowing system at PT.X.